1995
DOI: 10.1111/j.1469-8137.1995.tb04295.x
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of soil fertility and atmospheric CO2 on leaf area growth and carbon gain physiology in Populus×euramericana (Dode) Guinier

Abstract: SUMMARYTwo important proeesses whieh may limit produetivity gains in forest eeosystems with rising atmospheric CO, are reduction in photosynthetie capacity following prolonged exposure to high CO, and diminution of positive growth responses when soil nutrients, particularly N, are limiting. To exan-iine the interacting effects of soil fertility and CO^ enrichment on photosynthesis and growth in trees we grew hybrid poplar {Populus x euramericana) for 158 d in the field at ambient and twice ambient CO,^ and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
2
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 40 publications
7
69
2
1
Order By: Relevance
“…Elevated CO # has a direct effect on photosynthetic efficiency because it increases the diffusion gradient of CO # into leaves, and increases leaf N-use efficiency and the efficiency of photosynthetic enzymes (Drake & Gonza ' lez-Meler, 1997). This CO # -stimulation of A decreased following budset, possibly through carbohydrate feedback inhibition of photosynthesis, as seen in other Populus species before and after budset (Bosac et al, 1995 ;Curtis et al, 1995).…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated CO # has a direct effect on photosynthetic efficiency because it increases the diffusion gradient of CO # into leaves, and increases leaf N-use efficiency and the efficiency of photosynthetic enzymes (Drake & Gonza ' lez-Meler, 1997). This CO # -stimulation of A decreased following budset, possibly through carbohydrate feedback inhibition of photosynthesis, as seen in other Populus species before and after budset (Bosac et al, 1995 ;Curtis et al, 1995).…”
Section: mentioning
confidence: 99%
“…This was unexpected because several studies demonstrated substantial increases in stem height (c. 7-90 %), leaf area (c. 10-50 %), and above-ground biomass (c. 25-47 %) in five Populus hybrids in elevated CO # (Radoglou & Jarvis, 1990 ;Bosac et al, 1995 ;Curtis et al, 1995 ;Pregitzer et al, 1995 ;Ceulemans et al, 1996). However, Populus grandidentata, another naturally occurring species, had no significant height or leaf area response to elevated CO # (Curtis et al, 1994).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact poplars are the most promising trees for "short rotation intensive culture" (SRIC) [15]. In recent years several experiments were already carried out on the effects of atmospheric CO 2 on poplars [1,3,7,14,20,31,32,39], most of them for a limited duration of treatment (less than one year) and/or on individual plants.…”
Section: Introductionmentioning
confidence: 99%
“…A higher CO 2 concentration may also affect leaf respiration directly by as yet unknown modifications of the respiratory biochemistry (Amthor, 1991;Wullschleger et al, 1994) and indirectly through changes in growth rate and tissue composition (sugars, nitrogen) (Wullschleger et al, 1992a;Curtis et al, 1995). In trees, the CO 2 enrichment usually induced a reduction in leaf dark respiration (EI Kohen et al, 1991;Wullschleger et al, 1992b;Reid and Strain, 1994;Teskey, 1995 (Bradford, 1976 (Sheen, 1994 (Bonner, 1967;Laties, 1974).…”
Section: Introductionmentioning
confidence: 99%